A Guide to MATLAB for ME 160 - Bray, Austin; Montazami, Reza (Open textbook library., 2022)
This textbook provides an introduction to the MATLAB programming language for first-year mechanical engineering students enrolled in ME 160, Mechanical Engineering Problem Solving with Computer Applications. Designed to follow the content taught in class, this book provides a supplement to in-class learning that is presented at a level that is understandable to a student with no experience coding before coming to Iowa State University.